Digital Platforms’ Adoption by Educational Stakeholders in Private Secondary Schools During and after the Lockdown in Port Harcourt Local Government Area, Rivers State - Blaise, Ella Gogo; Awotua-Efebo, Ebi Bio (West African Journal of Open and Flexible Learning, 2024)
This study aimed to investigate the digital platforms used by teachers, students, and administrators in private secondary schools during and after the lockdown period necessitated by the COVID-19 pandemic. The research methodology employed was a descriptive survey. A multi-stage sampling procedure was utilised to select a sample size of seven hundred and forty-two (742) participants, comprising four hundred and nine (409) students, two hundred and ninety-seven (297) teachers, and thirty-six (36) administrators from thirty-two (32) private secondary schools in Port Harcourt, Rivers State. To collect data, three distinct questionnaires and an observation checklist were administered. The data analysis was done using frequency, ranking, and bar charts. The results revealed that a combination of digital platforms, including social media platforms, meeting applications, and learning management systems, were widely adopted for teaching, learning, and administrative purposes. It was observed that the social media platform, WhatsApp, emerged as the most adopted by teachers, students, and administrators during the lockdown period. However, post-lockdown, there was a discernible shift among teachers towards the adoption of learning management systems, especially Google Classroom. Administrators displayed a consistent reliance on social media platforms for their administrative duties. As a result of these findings, the researchers recommended that teachers, students, and administrators should further explore and fully leverage the features and capabilities of digital platforms to optimise their respective tasks and responsibilities. Résumé : Le but de cette étude était d’étudier les plateformes numériques utilisées par les enseignants, les élèves et les administrateurs dans les écoles secondaires privées pendant et après la période de confinement rendue nécessaire par la pandémie de Covid-19. La méthodologie de recherche utilisée était une enquête descriptive. Une procédure d’échantillonnage en plusieurs étapes a été utilisée pour sélectionner un échantillon de sept cent quarante-deux (742) participants, comprenant quatre cent neuf (409) élèves, deux cent quatre-vingt-dix-sept (297) enseignants et trente-six (36) administrateurs parmi trente-deux (32) Les écoles secondaires privées de Port Harcourt, dans l’État de Rivers. Pour recueillir les données, trois questionnaires distincts et une liste de contrôle d’observation ont été administrés. L’analyse des données a été effectuée à l’aide de la fréquence, du classement et du graphique à barres. Les résultats ont révélé qu’une combinaison de plateformes numériques, y compris des plateformes de médias sociaux, des applications de réunion et des systèmes de gestion de l’apprentissage, a été largement adoptée à des fins d’enseignement, d’apprentissage et d’administration. On a observé que la plateforme de médias sociaux, WhatsApp, est devenue la plus adoptée par les enseignants, les élèves et les administrateurs pendant la période de confinement. Cependant, après le confinement, il y a eu un changement perceptible parmi les enseignants vers l’adoption de systèmes de gestion de l’apprentissage, en particulier Google Classroom. Les administrateurs ont toujours fait appel aux plateformes de médias sociaux pour leurs tâches administratives. En raison de ces résultats, les chercheurs ont recommandé que les enseignants, les étudiants et les administrateurs continuent d’explorer et d’exploiter pleinement les caractéristiques et les capacités des plateformes numériques afin d’optimiser leurs tâches et responsabilités respectives. Mots-clés : Plateforme numérique, Enseignant, Étudiant, Administrateur, Enseignement secondaire